Applying systems thinking and active learning strategies to a lean manufacturing program (2010)
Lean Manufacturing seeks to eradicat e waste. This pursuit is conducted changing many pre-conceptions inherited fr om the mass production traditions. It is necessary to understand immediate and delayed impacts of the changes, as well as direct and indirect results of these changes. Th is systemic approach should enhance the learner’s understanding of the system (the manufacturing company) , its variables, its outcomes, and the relationships among the system’s components. This paper presents the process of designing a course to teach Lean Manufacturing to working professionals using systems thinking. This design proce ss is conducted for the development of job competencies and using Active Learning Strategies.